Gadolinium to the rescue for mechanical thrombectomy in acute ischemic stroke. Issue 3 (June 2019) - Male, Shailesh; Mehta, Tapan; Tore, Huseyin; Quinn, Coridon; Grande, Andrew W; Tummala, Ramachandra P; Jagadeesan, Bharathi D
Introduction: Mechanical thrombectomy in the setting of acute ischemic stroke (AIS) requires cerebral digital subtraction angiography (DSA), typically performed with iodinated contrast medium. We present a case of emergent cerebral DSA and mechanical thrombectomy using gadolinium-based contrast for cerebral DSA in a patient with a history of anaphylaxis to iodinated contrast agents (ICs). Case report: A 72-year-old man developed left ventricle assist device thrombus while on anticoagulation. During hospitalization he suffered right middle cerebral artery occlusion with a National Institutes of Health stroke scale score of 10. He had a history of anaphylaxis and the advanced directives revealed do not resuscitate/do not intubate status. We performed an emergent DSA as part of thrombectomy procedure using gadolinium-based contrast mixed in 1:1 proportion with normal saline. The images obtained were of adequate quality and the patient underwent successful thrombectomy with modified thrombolysis in cerebral infarction 2B recanalization. Conclusion: Gadolinium-based contrast agents could be effective alternatives for cerebral DSA in patients undergoing mechanical thrombectomy for AIS who have a history of anaphylactic reaction to ICs.